The effect of COVID-19 on foreign direct investment - Kazunobu Hayakawa; Hyeon hun I; Cyn-Young Park (Asian Development Bank (ADB), 2022)
This study empirically examines how the coronavirus disease (COVID-19) has impacted foreign direct investment (FDI), using the quarterly data on bilateral FDI flows from 173 home to 192 host countries from the first quarter of 2019 to the second quarter of 2021. We measure the severity of COVID-19 damage using three indicators-the number of confirmed cases, the number of deaths, and the stringency index of government policies that restrict people's activities. We also differentiate FDI flows via two different entry modes-greenfield FDI and cross-border mergers and acquisitions (M&A). We find heterogeneous effects of COVID-19 impacts on FDI by sector and entry mode. The severity of COVID-19 in host countries adversely affected FDI in the manufacturing sector regardless of the entry mode, but the effect of home countries' COVID-19 situation on FDI was insignificant. On the other hand, in the service sector, the severity of COVID-19 in both host and home countries has significantly negative impact on greenfield FDI, not on cross-border M&A.
Keywords: F21; F23; I15; 330; COVID-19; greenfield FDI; cross-border M&A